Induction chemoimmunotherapy may achieve non-inferior outcomes to consolidation immunotherapy in patients with unresectable stage III NSCLC: a real-world multicenter retrospective study - Song Guan; Song Guan; Yu Wang; Qing Liu; Meng Yan; Kai Ren; Jun Wang; Nan Bi; Lujun Zhao (Frontiers in Immunology)
BackgroundConsolidation immunotherapy after chemoradiotherapy (CRT) is the standard of care for unresectable stage III non-small cell lung cancer (NSCLC). However, the role of upfront chemoimmunotherapy before CRT remains unclear. This study aims to investigate the value of induction chemoimmunotherapy before CRT in unresectable stage III NSCLC.MethodsUnresectable stage III NSCLC patients who received induction chemoimmunotherapy before CRT or consolidation immunotherapy after CRT from four centers were retrospectively enrolled. The Kaplan-Meier method was used to estimate progression-free survival (PFS) and overall survival (OS), and one-to-one propensity score matching (PSM) was used to further minimize confounding.ResultsA total of 262 patients were enrolled, with 124 (47.3%) receiving induction chemoimmunotherapy (Ind group) and 138 (52.7%) receiving consolidation immunotherapy (Con group). Further 1:1 PSM analysis showed that induction chemoimmunotherapy achieved comparable outcomes to consolidation immunotherapy (2-year PFS: 56.0% vs. 45.6%, P=0.327; 2-year OS: 81.0% vs. 79.2%, P=0.960) with fewer cycles of immunotherapy (median 4 vs. 10 cycles, P<0.001). The incidence of treatment-related adverse events was similar (P>0.05). Exploratory analysis found that patients with < 4 cycles of induction immunotherapy had similar PFS (median NR vs. 30.1 months, 2-year PFS 50.8% vs. 54.4%, P=0.932) but prolonged OS (median NR vs. 46.0 months, 2-year OS 89.0% vs. 75.5%, P=0.112) compared to those with ≥ 4 cycles of induction immunotherapy.ConclusionUpfront chemoimmunotherapy before CRT appears to be feasible and safe, and may achieve non-inferior outcomes to consolidation immunotherapy with fewer cycles of immunotherapy.